Coordination in track & field sprinters while performing the countermovement jump - Preatoni, E.; Devodier, E.; Andreoni, G.; Rodano, R. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The aim of this study was to assess coordination, coordination variability and their evolution with time, during the countermovement jump. For this purpose a population of track & field sprinters was analysed through a Dynamic Systems approach. Five testing sessions over the year were considered. The kinematics of lower limbs was recorded by an optoelectronic system, and the continuous relative phase of the hip-knee and knee-ankle joints was considered. Results showed different behaviours for the two couplings across the functional phases of the movement, with an increased variability and a less in-phase relationship during transitions between phases. No relevant changes were reported over the subsequent testing sessions.